Tensile bond strength of fiberglass and anatomized posts - Herbert Cosio Dueñas; Irma Soledad Vilavila Huarancca; Liceth Lazo Otazú; Danitza Garate Villasante (Editorial Ciencias Médicas, 2021)
Introduction: Fiberglass posts often fall off their position due to loss of adhesive capacity when they are subjected to masticatory force. Objective: Compare in vitro the tensile bond strength of fiberglass and anatomized posts cemented with the same adhesive material. Methods: An in vitro experimental study was conducted. A selection was made of 20 premolars extracted by orthodontic indication which were then randomly distributed into two groups. The premolars underwent root canal treatment by a specialist. The preparation was manual and sealing was performed by lateral condensation. The teeth were prepared in the standard manner to receive the fiberglass and resin-anatomized posts. In both groups' cementation followed the protocol suggested by the manufacturer of Allcem Core® (dual cement). The specimens were stamped in self-curing acrylic. Next, they were subjected to vertical tensile strength in an materials testing machine (Instrom©). Results: The mean values obtained were 31 kg/F for teeth with anatomized posts and 12.47 kg/F for fiberglass posts. According to Shapiro-Wilk tests, the samples exhibited a normal distribution (p > 0.05). The hypothesis was contrasted with Student's t test, obtaining a highly significant statistical difference between the groups (p = 0.001). Conclusions: Vertical tensile bond strength is greater in anatomized posts.